Slips, Stumbles, and Falls: Pedestrian Footwear and Surfaces 1990
DOI: 10.1520/stp15500s
|View full text |Cite
|
Sign up to set email alerts
|

Slip Resistance Needs of the Mobility Disabled During Level and Grade Walking

Abstract: Slip resistance needs were compared between mobility disabled and able-bodied individuals. Subjects walked across a level piezoelectric force plate at slow and fast speeds, and the ratio of the total shear force to the normal force was used as the required coefficient of friction (μr) Near touchdown,μr was found to be significantly greater (p < 0.05 for all significance values) for the mobility disabled (0.64 ± 0.19) than for the able-bodied (0.31 ± 0.07), regardless of the speed of walking. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 4 publications
1
31
2
Order By: Relevance
“…The double support period, expressed as a percentage of the total support period, lengthened and the single support period shortened significantly as the load increased. Buczek et al (1990) emphasized that the slip resistance needs for mobility disabled may be greater than for able-bodied persons. Their study indicated that the required coefficient of friction near touch-down for the unaffected side of the mobility disabled person was significantly higher (average 0.64) than for the able-bodied (average 0.31) regardless of the speed (slow or fast) of walking, whereas no difference was observed for the push-off phase.…”
Section: Manual Exertionmentioning
confidence: 99%
“…The double support period, expressed as a percentage of the total support period, lengthened and the single support period shortened significantly as the load increased. Buczek et al (1990) emphasized that the slip resistance needs for mobility disabled may be greater than for able-bodied persons. Their study indicated that the required coefficient of friction near touch-down for the unaffected side of the mobility disabled person was significantly higher (average 0.64) than for the able-bodied (average 0.31) regardless of the speed (slow or fast) of walking, whereas no difference was observed for the push-off phase.…”
Section: Manual Exertionmentioning
confidence: 99%
“…The new pattern that emerges in such a situation can be affected by many factors, for instance, the gender [1] and/or some pathological condition [2][3][4][5][6]. However, with few exceptions [7], most of the stroke gait studies have focused on measuring the walk in rehabilitation environments which may be less complex than the environment typically encountered in the home setting.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that peak RCOF varies with age [1], gender [1], limb dominancy [11,12] and the presence of a disability [2][3][4][5][6]. Those with a disability would appear to be at potentially greater risk owing to the largest changes in gait characteristics and GRFs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations